2011
DOI: 10.2319/021411-108.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of vestibular recession in mandibular incisors after orthodontic treatment

Abstract: Objective: To assess the prevalence and severity of vestibular gingival recession of mandibular incisors after orthodontic treatment and to evaluate possible contributing factors. Materials and Methods: From the record pool of patients who completed orthodontic treatment from 1999-2006 at the Department of Orthodontics, University of Oslo, Norway, 588 patients fulfilled the inclusion criteria. Intraoral color slides were used for the evaluation of gingival recessions (based on Miller classification), presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 27 publications
2
39
0
12
Order By: Relevance
“…pointed to an increased incidence of labial recessions in cases of dentoalveolar compensation of class III malocclusion [21]. Their findings are supported by the observation that pre-treatment existent recessions and the retroclination of teeth in cases of mesiobasal relation constitute key risk factors for the development of further recessions [22]. Therefore, careful treatment planning and consideration of all relevant parameters and the subsequent transfer of the anticipated tooth position to the clinical situation are crucial for a successful treatment outcome.…”
Section: Introductionmentioning
confidence: 93%
“…pointed to an increased incidence of labial recessions in cases of dentoalveolar compensation of class III malocclusion [21]. Their findings are supported by the observation that pre-treatment existent recessions and the retroclination of teeth in cases of mesiobasal relation constitute key risk factors for the development of further recessions [22]. Therefore, careful treatment planning and consideration of all relevant parameters and the subsequent transfer of the anticipated tooth position to the clinical situation are crucial for a successful treatment outcome.…”
Section: Introductionmentioning
confidence: 93%
“…It was found that mandibular incisors were particularly prone to develop recession. [3][4][5][6]9,18 In a population of orthodontically treated patients with fixed lingual retainers 5 years after treatment, the highest recession frequency was registered for the central incisors, then for the canines, and least for the mandibular lateral incisors. 5 The present study showed that canines in the group without retainers had the highest frequency, followed by canines and central incisors in the retainer group.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Mandibular central incisors have been shown to be particularly susceptible to the development of gingival recession. 5,9 Compared with untreated controls, the prevalence of gingival recession in mandibular incisors was found to be higher in patients 5 years after orthodontic treatment. 3 It is unclear whether orthodontic treatment per se, proclination of incisors, 10 or the presence of fixed retention has more influence on the development of gingival recession, 3,11 but the type of fixed retainer did not seem to play a significant role.…”
Section: Introductionmentioning
confidence: 95%
“…However, Vasconcelos et al [9] found that retroclination was also related to an increase in the severity of gingival recession. On the other hand, Djeu et al [26] did not find a correlation between the proclination of mandibular central incisors and gingival recession.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial, the scientific evidence demonstrates that gingival recession can develop in patients who undergo orthodontic movement [8, 9]. Furthermore, some studies have confirmed a positive correlation between the increase of severity and extension of gingival recession and orthodontic treatment [10].…”
Section: Introductionmentioning
confidence: 99%